Development of sustainable performance model based on LM, QMS, SOFT TQM, and EMS : Malaysian context - Khalili, Amjad M R (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
Organizations are trying to become World Class Manufacturing (WCM) by implementing the best practices of Operations Management (OM). Sustainable Performance (SP) is a common target to be achieved and maintained by any manufacturing organization. In this regard numerous studies have been carried out on essential key Operations Management (OM) practices namely Lean Manufacturing (LM), Soft TQM (STQM), Quality Management System (QMS), and Environmental Management System (EMS) with a view to assessing the impact on SP. However, most of these studies were conducted separately at manufacturing industries in different parts of the world and found to be inadequate to explore whether these practices are integrated together in the same enterprise or not in a holistic manner. In this context an attempt is made to develop a conceptual model by investigating the linkages among these key OM practices and inaugurating their associative interrelationships based on feedback from industrial managers through an exhaustive survey in Malaysia. The model encapsulates that LM is the exogenous, SP is the endogenous construct while three practices namely QMS, STQM and EMS are proposed as mediators. For this empirical investigation of the model, twenty (20) hypotheses were postulated. Both qualitative and quantitative techniques were adopted. Primary data were gathered through three stages. Initially a semi-structured interview was conducted to explore the model applicability by the verbatim responses gathered from fifteen managers. Then a pilot study was done by using the responses gathered through a structured survey questionnaire relating to the OM practices distributed among 240 operations managers in different certified manufacturing industries. For the final stage of the study a wider survey was done by distributing 900 questionnaires to the managers of manufacturing industries in Malaysia via both postal and web-based survey. Principal Component Analysis (PCA) was exploited from SPSS22 for data reduction whereas Confirmatory Factor Analysis (CFA), structural model and bootstrapping technique were adopted from Structural Equation Modeling (SEM) AMOS 22 for examining model validity and hypotheses testing. Findings from the thematic analysis demonstrate that managers are adequately aware of these practices as these are aligned with OM theories and the developed model is supported. PCA show that all the model constructs are deemed reliable. The range of Kaiser Meyer Olkin (KMO) values for latent constructs lie between 0.69 and 0.85. Seven components for LM, while three components for each of the practices, QMS, STQM, EMS and SP were extracted and found to be considered as the critical success factors by the manufacturers for successful implementation. The study found that three practices such as QMS, STQM, and EMS were performing as mediators. Seven causal hypotheses were supported, whereas six mediated hypotheses were supported. The developed model can be preserved as an “eye opener” primarily for the local operations managers to implement the identified initiatives to help achieve Malaysia' vision of becoming a developed nation in foreseeable future. Nevertheless, this study results can be treated as a guiding portfolio for manufacturing operations elsewhere.